THE AESTHETICS OF SCULPTURAL FORMS EXECUTED FROM MARL STONE: AN APPLIED STUDY - Amer Khalil Nasser (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research included the aesthetics of sculptural forms executed from the material of Marl stone in sculpture as an alternative to marble (an applied study). Four chapters about me, the first chapter on the methodology of the research that defined its problem, its importance, the need for it, the goal of the research and its limits, defining its terminology, and determining the problem of his research by the following question: Is there aesthetic For the forms executed from the material marl stone in sculpture as an alternative to marble? As for the second chapter, it concerned me with the theoretical framework, which contained two topics. The first topic concerned with the aesthetic experience between philosophy and application. As for the third chapter, it was devoted to the research procedures, the research sample was defined, its methodology, the experiment was conducted and access to the formal formulas in the application side. The fourth chapter was concerned with the results, conclusions and recommendations and the most important results were the researcher relying on the energy inherent in the stone material itself to suggest the expressive and aesthetic dimensions according to the performance of the show depends To control the system of form, which is an effective tool and influences the aesthetic perception of the recipient. In the current experiment, the stone material constituted a malleable tool in expressing the visual language involved in the sculptural products because of its fertile potential in shaping, which the researcher tested and considered a suitable medium through which he reflected aesthetic and cognitive values in the mind of the recipient. The most important conclusions are that the stone material was not just a material medium that transmits the form, but rather a physical medium that contributed greatly to reviving the aesthetic values in the construction of the sculptural work. The formal diversity of the sculptural product in the current experience represented a reflection of the perceived self that worked to placate the ideas attached to the mental imagination, which contributed to the production of sculptural works of an innovative nature.